Keeping Science on Keel When Software Moves. - AHN, DONG H.; BAKER, ALLISON H.; BENTLEY, MICHAEL; BRIGGS, IAN; GOPALAKRISHNAN, GANESH; HAMMERLING, DORIT M.; LAGUNA, IGNACIO; LEE, GREGORY L.; MILROY, DANIEL J.; VERTENSTEIN, MARIANA (Communications of the ACM, 2021)
The article examines the problem of false or misleading conclusions in science that stem from difficulties in reproducibility associated with porting more efficient scientific software in high performance computing (HPC). It discusses the concept of bisection, statistical combinations testing in the Community Earth System Model (CESM), and the FLiT workflow.